Pengembangan Ekowisata Poncokusumo melalui Grand Strategy Matrix Analysis - Bambang Supriadi (Universitas Merdeka Malang, 2018)
The purpose of this study is to find a strategic position for the development of ecotourism in Poncokusumo through the Grand Strategy Matrix Analysis. The study was conducted in Poncokusumo, 80 km to south from Malang. The samples of this study were consisting of Tourists, Pokdarwis, local community and tourist destination management, totaling 100 respondents. Sampling in this study was based on purposive sampling technique. This study used SWOT analysis (structure, Weakness, Opportunity and Threats) through 6 (six) stages: 1) Determining Ecotourism SWOT Indicators; 2) Weighting of SWOT values; 3) Determination of the value of the measuring scale; 4) Weighted value formulations; 5) Calculate the weighted value difference; 6) Making a Grand Strategy for the SWOT analysis matrix (Aggressive, Turn around, Survival, Diversification). The results of this study indicate that Poncokusumo ecotourism is in the first position of consciousness (0.4: 0.85) which means that the attraction of ecotourism has the strength and opportunity to be developed, so the strategy that needs to be implemented in order to maximize the strength of tourist attractions in the form of natural tourism, ecology sustainable and community empowerment (tourism conscious groups) as well as taking advantage of opportunities because of tourism service support, high tourist motivation for interest in visits to the attraction of eco-tourism and the lack of tourist competitors.